Reflections on the New Deal: The vested interests, limits to reform, and the meaning of liberal democracy - John F. Henry (Levy Economics Institute of Bard College, 2018)
I subject some aspects of Roosevelt's "New Deal" to critical analysis, with particular attention to what is termed "liberal democracy". This analysis demonstrates the limits to reform, given the power of "vested interests" as articulated by Thorstein Veblen. While progressive economists and others are generally favorably disposed toward the New Deal, a critical perspective casts doubt on the progressive nature of the various programs instituted during the Roosevelt administrations. The main constraint that limited the framing and operation of these programs was that of maintaining liberal democracy. The New Deal was shaped by the institutional forces then dominant in the United States, including the segregationist system of the South. In the end, vested interests dictated what transpired, but what did transpire required a modification of the understanding of liberal democracy.
Keywords: B52; N2; N4; P1; 330; Vested Interests; New Deal; Planning; Liberalism